ANALISIS POTENSI TINGKAT BENCANA BANJIR DAERAH ALIRAN SUNGAI WAY KURIPAN KOTA BANDAR LAMPUNG - Ayudia Hardiyani Kiranaratri; Nirmawana Simarmata; Denny Hidayat (Rekayasa Sipil, 2019)
Floods are always a problem, especially in residential areas. This is in line with the development of people's lives. The Way Kuripan River is a river that passes through several villages in the city of Bandar Lampung, which often overflows into community settlements if the rainy season arrives, especially in the Pesawahan, Kuripan and Karang Cities which are downstream from the river. Therefore, it is necessary to have an analysis to find out the river water level that passes through an area if the rainy season arrives whether or not it can be accommodated by the river body or not. Based on the survey in the field, it is known that the width of the Way Kuripan River is found in the Betung Hills, West Tanjung Karang District, which is 20 m and the depth of the river is 4.51 m. if the rainy season arrives, the upper reaches of the Way Kuripan River have a water level that is 0.5 m - 3.0793 m so that the depth of the river is still able to be accommodated by different river bodies with downstream rivers in Pesawahan and Karang Cities where due to sedimentation the depth of the river is only 2.78 m and the width of the river is 10 m, while during the rainy season the river water level reaches 0.5 - 5,216 m. so that the water that passes through is unable to be accommodated in the river body and overflows in the area.